Temperature Estimation and Comparison with Deep Learning and Statistical Modeling Method - Sevinç, Aynur; Kaya, Buket (Osman SAĞDIÇ, 2021)
It is important that the air temperature forecast includes high accuracy, especially for countries that have come to the fore with their agriculture-based economies in recent years. Forecasting becomes more complex due to constantly changing weather conditions. Some mathematical and statistical techniques may be insufficient to provide temperature estimation. At this point, deep learning methods emerge as popular methods that have been accepted in recent years in making this process more successful. Successful weather forecasting studies can be done with deep methods that perform an effective climate analysis. The purpose of this article is to demonstrate the applicability of various deep learning and temporal series analysis methods for air temperature prediction based on meteorological data and compare the performance results. In order to carry out this study, analyzes were made with deep neural network Long Short Term Memory (LSTM) and Autoregressive Integrated Moving Average (ARIMA) models, using meteorological data from Solhan district of Bingöl province in the Eastern Anatolia Region of Turkey. In the results of the experiments on the real data set, successful results were obtained in the prediction of the future temperature. The predictive performance of these models was compared using different evaluation metrics. The R square score value, which shows the relationship between the actual values and the estimated values, was calculated as 0.95 in the LSTM networks and 0.97 in the ARIMA model. The high estimation accuracy of the models has shown that these models can be successfully applied in temperature time series estimation studies.

Hava sıcaklığı tahmininin son yıllarda özellikle tarıma dayalı ekonomileriyle öne çıkan ülkeler için yüksek doğruluk içermesi önemlidir. Sürekli değişen hava şartları nedeniyle tahmin daha karmaşık hale gelmektedir. Bazı matematiksel ve istatistiksel teknikler sıcaklık tahmini sağlamada yetersiz olabilmektedir. Bu noktada derin öğrenme yöntemleri bu süreci daha başarılı hale getirmede son yıllarda kabul gören popüler yöntemler olarak karşımıza çıkmaktadır. Etkili bir iklim analizi gerçekleştiren derin yöntemler ile başarılı hava tahmini çalışmaları yapılabilmektedir. Bu makalenin amacı, meteorolojik verilere dayalı hava sıcaklığı tahmini için çeşitli derin öğrenme ve zamansal seri analizi yöntemlerinin uygulanabilirliğini göstermek ve performans sonuçlarını karşılaştırmaktır. Bu çalışmanın gerçekleştirilmesi için Türkiye’nin Doğu Anadolu Bölgesi’nde yer alan Bingöl ilinin Solhan ilçesine ait meteorolojik veriler kullanılarak, derin sinir ağı Uzun Kısa Süreli Bellek (LSTM) ve Otoregresif Entegre Hareketli Ortalama (ARIMA) modelleri ile analizler yapılmıştır. Gerçek veri kümesi üzerinde yapılan deney sonuçlarında geleceğe yönelik sıcaklık tahmininde başarılı sonuçlar elde edilmiştir. Bu modellerin tahmine dayalı performansları farklı değerlendirme metrikleri kullanılarak karşılaştırılmıştır. Gerçek değerler ile tahmini değerler arasındaki ilişkiyi gösteren R kare skoru değeri LSTM ağlarında 0.95, ARIMA modelinde ise 0.97 olarak hesaplanmıştır. Modellerin tahmin doğruluğunun yüksek olması, sıcaklık zaman serisi tahmini çalışmalarında bu modellerin başarılı bir şekilde uygulanabileceğini göstermiştir.
Derin Öğrenme ve İstatistiksel Modelleme Yöntemiyle Sıcaklık Tahmini ve Karşılaştırılması
Keywords: Engineering; Mühendislik